Bibliometric Study: Trends of Development Digital Media to Improve 21st Century Students' Skills in Physics Learning - Mohamad Wahdiansyah Arrahmat; Mita Anggaryani; Oka Saputra; Noval Maleakhi Hulu (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: This bibliometric study aims to analyze trends in the development of digital media to enhance 21st-century skills among students in physics learning. It seeks to map research patterns, identify key contributions, collaborations, and emerging themes, while highlighting gaps in the application of interactive digital tools like animations, virtual reality (VR), and augmented reality (AR) to foster critical thinking, creativity, collaboration, and communication in physics education. Method: This study used method with a bibliometric literature review was conducted using data from the Scopus database and analyzed using VOSviewer and Microsoft Excel. Results: The study's results, which show a significant increase in publication trends post-2020, peaked at 47-79 articles annually, driven by COVID-19-induced shifts to online learning. Key co-occurrence networks revealed dominant keywords like